Atividade docente de estudo de professoras do ciclo de alfabetização: vivências formativas em contextos de cultura escrita - Millani, Silvana Martins de Freitas (2017)
This study is linked to the Training, Knowledge and Professional Development Line of the Graduate Program in Education of the Federal University of Santa Maria / RS. The following question is presented as a guiding problem: how is the teaching activity of the study of teachers of the literacy cycle developed in contexts of written culture? Based on this problem, it was defined as a general objective: to understand the development of the teaching activity of the study of teachers of the literacy cycle in contexts of written culture. For that, specific objectives were defined as: identifying the formative experiences in contexts of written culture of teachers of the literacy cycle; recognizing how the formative experiences in contexts of written culture have repercussions on the development of the teaching activity of the teachers; Identifying the procedures and strategies, as well as the actions and operations involved in the process of developing the teaching activity of the teachers' study; And recognizing how the teaching activity of study has repercussions on the learning of the teaching of the teachers. In this perspective, the qualitative methodological approach of sociocultural approach was based on the studies of Vygotski (2007, 2010), Bakhtin (2010a, 2010b), Clandinin and Connely (1995), Freitas (2002, 2007) and Bolzan (2001, 2002), whose theoretical and methodological assumptions contributed to the analysis of the narratives of seven teachers of the literacy cycle, who were constituted as collaborators of the research . From the theoretical subsidies of Vygotsky (1996, 2007, 2009, 2010, 2012, 2013, 2014), Leontiev (1978, 1984), Davidov and Markóva (1987), Marcelo Garcia (1999), Imbernon Tardif (2014), Ferry (2004), Zeichner (1993), Schön (1997), Nóvoa (1997), Ferreiro (2001, 2010, 2013), Ferreiro and Teberosky (1999), Bolzan (2001, 2002, 2009, 2016a ) And Isaia (2006), among other references, the theoretical-analytical framework of this study was developed, defining as a great category the teaching activity of study and as its categorical dimensions the formative experiences and the production of teaching. In this plot, the movements of sense production and shared learning are also present, as well as the transversal element that is configured by the self, hetero and interformative actions. The research made it possible to understand that the development of the teaching activity of study is consolidated through multiple formative experiences that constitute the personal and professional trajectory of the teachers. In this process, pedagogical practice is recognized as the main activity of teachers, which generates the needs and motivations that drive the teaching activity of study. In addition, the teachers show in their narratives that this activity is enhanced by the collaborative activity produced in the study group, favoring the construction of shared pedagogical knowledge capable of promoting pedagogical autonomy and leverage the learning processes of literacy teaching. Finally, it is possible to affirm that the organizational movement of the teaching activity of study is a permanent process, which is being promoted and re-dimensioned by the movements of shared learning and production of meaning, generating a way of constitution of self in teaching, that is, a way of learning to be a teacher.